Bantul Integrated Sirine System (BISS) as a Bantul Regency Preparedness in Dealing with Tsunami Hazard - Iffani, Maulida; Yunita Putri, Ardya; Efendi, Eta Nur (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
Bantul Regency is directly adjacent to the Indian Ocean and has a long coastline of 17 km (Marine and Fishery Service of Bantul Regency, 2017). There are at least 3 sub-districts with 11 coastal villages in Bantul Regency directly adjacent to the Indian Ocean. These sub-districts include Kretek, Sanden and Srandakan sub-districts. That is, there are 11 villages from 3 sub-districts in Bantul Regency directly exposed to tsunami threat from the Indian Ocean. There are the uncertainty of tsunami information in community. an Early Warning System (EWS) is needed to reduce the risk of a tsunami disaster and improve the existing evacuation system in the southern coastal area of Bantul District. With the information clarity of the tsunami disaster then the evacuation process will be more tersistem and neatly so that the panic of citizens will be reduced when the symptoms of a disaster occurred. this study has the objectives of (1) Identifying BISS as a means of disseminating tsunami early warning spreaders (2) Identifying the influence of BISS in improving community preparedness of Bantul Regency in facing the threat of tsunami disaster. The result show that Bantul Integrated Sirine System (BISS) is one form of tsunami early warning system built in Bantul Regency using sedrhana technology which is independently assembled by Bantul Regency and utilize the existence of community settlement location in tsunami early warning dissemination. The sustainability of tsunami early warning is certainly expected by all parties. Because the positive impact of this innovation is very important in reducing the risk of tsunami disaster. This early warning sustainability can be done because it is supported in a constitutional, and technological manner